Pathology and management of masses in the accessory parotid gland region: 24-year experience at a single institution. Issue 2 (February 2018) - Ma, Hailong; Jin, Shufang; Du, Zhong; Wang, Lizhen; Zhang, Zhiyuan; Wang, Yan'an
Abstract: Purpose: Masses in the accessory parotid gland (APG) region are clinically rare and their management can lead to conflicts between the need for tumor resection and facial cosmesis. The aim of this study was to analyze the pathological classifications and management of APG lesions in our hospital. Materials and methods: From January 1993 to March 2017, 130 patients with primary tumors in the APG region who underwent surgical treatment were enrolled. Follow-up surveys after surgery were then carried out. Results: Among the 130 patients, 53.8% of lesions were benign ( n = 70), 23.8% were malignant ( n = 31), 14.6% were vascular malformations ( n = 19), 6.15% were sialadenitis ( n = 8), and 1.65% were cysts ( n = 2). Pleomorphic adenoma accounted for 67.1% of the benign tumors ( n = 47). Lymphoma, lymphoepithelial carcinoma, and acinar cell carcinoma topped the list of malignant tumors (5 cases in each group). Surgery and surgery plus radio-chemotherapy were performed for benign and aggressive malignant lesions, respectively. At the time of follow-up, 5-year overall survival was 88.1%; mean follow-up was 139 months (range 3–281 months). Conclusions: Masses in the APG region have complicated pathological types. Perfect preoperative preparation, with fine-needle aspiration biopsy and imaging examinations, would contribute to identifying characteristics. Treatment schedules and surgical approaches should be determined according to the cytology reports and frozen-section examinations before and during operation.